ISLAM MODERAT DALAM PENDIDIKAN MADRASAH: IMPLEMENTASI NILAI TOLERANSI, KEADILAN, DAN KESEIMBANGAN DI MAS MUHAMMADIYAH SUKARAME - Yosa Yuwanda; Eti Hadiati; Evi Febriani (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
The implementation of moderate Islamic values has become an essential concern in Islamic education, as madrasahs function not only as spaces for transmitting religious knowledge but also as institutions for cultivating students’ character as tolerant, just, balanced, and respectful individuals. This study focuses on the application of moderate values in Islamic Religious Education learning and the challenges encountered in implementing moderate Islamic values at MAS Muhammadiyah Sukarame. Employing a descriptive qualitative approach, the study drew on primary data from the madrasah principal, Islamic Religious Education teachers, and students, as well as secondary data from institutional documents and supporting activity records. Data were collected through semi-structured interviews, observation, and documentation. The research stages included determining the research focus and informants, developing interview and observation guidelines, collecting field data, reducing data, presenting data, drawing conclusions, and validating the findings through technical triangulation. The findings reveal that moderate Islamic values are implemented through Islamic Religious Education learning, religious habituation, school activities, discussion, advice, role modelling, and a culture of mutual respect. The values manifested include tolerance, deliberation, cooperation, justice, discipline, and respect for differences. The main challenges include the low discipline of some students, limited responsiveness to advice, and a lack of variation in instructional media. This study concludes that the implementation of moderate Islamic values needs to be strengthened through more contextual, participatory, and sustainable learning so that moderation is not merely understood conceptually, but becomes part of students’ moral habits. ABSTRAK Implementasi nilai-nilai Islam moderat menjadi kebutuhan penting dalam pendidikan Islam karena madrasah tidak hanya berfungsi sebagai ruang transfer pengetahuan agama, tetapi juga sebagai tempat pembentukan karakter peserta didik yang toleran, adil, seimbang, dan mampu menghargai perbedaan. Penelitian ini berfokus pada penerapan nilai-nilai moderat dalam pembelajaran Pendidikan Agama Islam serta tantangan dan kendala dalam mengimplementasikan nilai-nilai Islam moderat di MAS Muhammadiyah Sukarame. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan sumber data primer dari kepala madrasah, guru Pendidikan Agama Islam, dan peserta didik, serta data sekunder dari dokumen madrasah dan bukti kegiatan pendukung. Data dikumpulkan melalui wawancara semi-terstruktur, observasi, dan dokumentasi. Tahapan penelitian meliputi penentuan fokus dan informan, penyusunan pedoman wawancara dan observasi, pengumpulan data lapangan, reduksi data, penyajian data, penarikan kesimpulan, serta pengujian keabsahan data melalui triangulasi teknik. Hasil penelitian menunjukkan bahwa nilai Islam moderat diterapkan melalui pembelajaran PAI, pembiasaan keagamaan, kegiatan sekolah, diskusi, nasihat, keteladanan, dan budaya saling menghargai. Nilai yang tampak meliputi toleransi, musyawarah, kerja sama, keadilan, disiplin, dan penghormatan terhadap perbedaan. Kendala utama meliputi rendahnya kedisiplinan sebagian siswa, sikap kurang responsif terhadap nasihat, serta terbatasnya variasi media pembelajaran. Penelitian ini menyimpulkan bahwa implementasi nilai Islam moderat perlu diperkuat melalui pembelajaran yang lebih kontekstual, partisipatif, dan berkelanjutan agar nilai moderasi tidak hanya dipahami, tetapi juga menjadi kebiasaan moral peserta didik.